Sport nutrition - Jeukendrup, Asker E. 1969-; Gleeson, Michael 1956- (Human Kinetics, 2019)
Sport Nutrition, Third Edition, uses a physiological basis to provide an in-depth look at the science supporting nutrition recommendations. Students will come away with an understanding of nutrition as it relates to sport and the influence of nutrition on performance, training, and recovery.